SWOT ANALYSIS IN THE CASE OF PUBLIC PERCEPTION SURVEY OF GOVERNMENT POLICIES IN INDONESIA - Feby Milanie; Rizki Dafari Tarigan; Majid Alfariz; Rangga Palansa; Muhammad Rasyid Sitindaon; Ahmad Nugraha Alfalaah; Andreas Sianturi; Rizki Tri Setiawan; Saut Mertua Aruan; Januardi Purba (Bulletin of Engineering Science, Technology and Industry, 2024)
This research has explored the strengths, weaknesses, opportunities and threats (SWOT) in implementing surveys on public perceptions of government policies in Indonesia. This survey is very important to obtain an accurate picture or data regarding public opinion, which can be used as a basis for making policies. The case study used is the basis for a survey conducted by the Central Statistics Agency (BPS) regarding fuel subsidy policies. The results of this research have provided insight into how survey design and implementation can be improved to produce more accurate and useful data.